Packet loss and packet delivery evaluation using network simulator for multicast enabled network nobility management - Mohd Aman, Hazana Afizah; Hassan Abdalla Hashim, Aisha; Mohd. Ramli, Huda Adibah; Islam, Shayla (Science & Engineering Research Support soCiety, 2017)
This paper investigates packet loss issue in multicast enabled network mobility management using network simulator. Network mobility management namely PMIPv6 has the capacity to reduce mobile IPv6 performance problems. But PMIPv6 basic architecture is limited to unicast communication. Therefore, this paper proposes PMIPv6 with context delivery and multicast fast reroute mechanisms to enable multicast services. In this paper, the configuration of multicast enabled PMIPv6 is done in network simulator called NS3. The aimed is to solve packet loss problem. This paper assumes that packet loss as the number of packets that are lost in a multicast communication. Packet loss is unescapable particularly in mobile multicast communication. It is a network system requirement to meet the threshold value of acceptable packet loss rate below than 5%. The packet loss ratio and the packet delivery ratio are extracted from the trace-file produced by the simulation process in NS3 simulator. The analyses of the packet loss ratio and packet delivery ratio are hereby presented. Keywords: NS3, Packet Loss, Packet Delivery, Mobile Multicast